Environmental politics : domestic and global dimensions - Vaughn, Jacqueline (Boston : Wadsworth Cengage Learning, 2011)
Our mission: At Wadsworth Political Science, our goal is to publish current, relevant programs that help instructors create lively, engaging classrooms. We aim to further inspire those students who are passionate about the discipline, and to motivate beginning students by showing them that they can, indeed, make a difference. --Book Jacket.
A historical framework for environmental protection -- Participants in the environmental debate -- The political process -- The lands debate -- Waste and toxics -- The politics of energy -- The politics of water -- Air quality : pollution and solutions -- Endangered species and biodiversity -- The global commons -- Population and sustainability -- Emerging issues in environmental politics.
Switzer, Jacqueline Vaughn.
Includes bibliographical references and index.
Keywords: Environmental policy